Role of Government of Malang Regency in Preserving Sustainable Wetlands - Dayusita, Debby (FIA UB, 2016)
This paper aims to discover the role of government of Malang Regency in preserving sustainable wetlands in order to materialize the Act No. 41/2009, as well as to measure a suitability between Spatial Plan and existing wetlands use. This study uses qualitative method by interviewing key persons from agencies which are involved in giving land use change permit known as wetland drying team. The result of the study shows the decrease area of wetlands is up to 12,265 Ha during 2009-2013 for various purposes, the implementation of spatial plan and coordination among members of wetland drying team are still weak, and an undesirable role of administrator in giving permit of land use change still occurs. The absence of spatial map scale 1:5000 causes the Act No. 41/2009 cannot be implemented well. Therefore, the Government of Malang Regency has to concern to the provision of proper spatial map. As the main actor of political and administrative function, the policy of preserving of sustainable wetlands highly depends on Regent of Malang.